Concept Analysis of IslamicTourism Development in Madura - Ahmad Faidlal Rahman (Jurnal VOK@SINDO, 2015)
This article describes the concept of islamic tourism development in Madura. This concept is considerably appropriate to the reality and condition of the religious society in Madura. The diversity of tourism attractions and religious cultures can make Madura become islamic and unique tourism destination in East Java and to encourage both domestic and international tourists to visit. This article aims to know the tourism potentials in Madura and to offer a concept of islamic tourism development in Madura. The data analysis was done qualitatively in which data collection was done to make abstraction instead of hypothesis testing. From the data colection and analysis, it can be concluded that the development of islamic tourism in Madura as is a way to preserve social and culture of Madurese and to create islamic touris as a special tourism in Madura.